DO ADOLESCENTS USE DATING APPS TO FIND SEXUAL PARTNERS? A STUDY OF MOTIVATION OF DATING APPS USE AMONG ADOLESCENTS IN INDONESIA - Baskoro, Andhika Ajie; Kistiana, Sari; Fajarningtyas, Desy Nuri; Hutasoit, Evalina Franciska (Universitas Airlangga, 2025)
Introduction: The existence of dating apps as a form of technological advancement has given individuals new ways to search for a romantic partner. Twenty-five percent of newlywed couples met through dating apps, while 40% of unmarried individuals were looking for partners online. Behind the search for a romantic partner through an app, some risks keep track of its users, which is associated with increased sexual activity. The use of dating apps for adolescent users should be a concern, given that, in the adolescent phase, initiation into sexual activity has become one of the frequently emerging aspects. Aims: To find out the motivation for using dating apps among adolescents aged 18-24 years old. Methods: The users’ motivation of the dating apps focuses on three aspects: Relationship Seeking, Sexual Experience, and Flirting which are categorized into low and high motivation. The study used a quantitative approach with data collection through online questionnaires on 151 respondents. This study used chi-square as its analytical tool. Result: The study showed that, of the three motivations, the motivation to find a lover was the most common among the participants. Regarding the socio-demographic characteristics, sex and the frequency of use of dating apps show significant association with sexual experience and flirting motivation. Age and region are associated with relationship-seeking and flirting motivation, respectively. Interestingly, relationship status is associated with sexual experience motivation. Conclusions: The study recommends increasing the provision of reproductive health information to minimize the risk of dating app use among adolescents.